2018
DOI: 10.1021/acs.bioconjchem.8b00146
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory CpG on Carbon Nanotubes Selectively Inhibits Migration of Brain Tumor Cells

Abstract: Even when treated with aggressive current therapies, patients with glioblastoma usually survive less than two years and exhibit a high rate of recurrence. CpG is an oligonucleotide that activates the innate immune system via Toll-like receptor 9 (TLR9) activation. Injection of CpG into glioblastoma tumors showed promise as an immunotherapy in mouse models but proved disappointing in human trials. One aspect of glioma that is not addressed by CpG therapy alone is the highly invasive nature of glioma cells, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 76 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…Although immunostimulatory oligonucleotide CpG was considered to activate TLR9 as well as initiate immune system to counteract GBM, its efficiency was proved disappointed in vivo. Darya et al [ 25 ] integrated CpG with SWCNT non-covalently, which assisted the delivery of CpG without affecting its therapeutic properties. They demonstrated that SWCNT/CpG inhibited the migration of GBM cells by inducing TLR9/ NF-κB pathway of macrophages.…”
Section: Carbon Allotropesmentioning
confidence: 99%
“…Although immunostimulatory oligonucleotide CpG was considered to activate TLR9 as well as initiate immune system to counteract GBM, its efficiency was proved disappointed in vivo. Darya et al [ 25 ] integrated CpG with SWCNT non-covalently, which assisted the delivery of CpG without affecting its therapeutic properties. They demonstrated that SWCNT/CpG inhibited the migration of GBM cells by inducing TLR9/ NF-κB pathway of macrophages.…”
Section: Carbon Allotropesmentioning
confidence: 99%
“…[ 417–419 ] Therefore, CpG‐ODNs‐based cancer therapies require careful consideration, as the stimulation of TLR9 receptor in some tumor cells could promote tumors growth and/or metastasis. [ 420,421 ] Optimizing the delivery systems and backbone modifications, partly overcome these limitations. Phosphorothioate modification of CpG‐ODN backbone, improve stability, and avoid DNases‐mediated degradation.…”
Section: Nonviral Gene Therapy Systemsmentioning
confidence: 99%
“…The co-delivery of a cytotoxic agent (doxorubicin-DOX) and a P-gp inhibitor (verapamil-VER) by oxMWCNT, resulted in a significant improvement in the DOX anticancer efficiency due to the increased drug uptake by leukemia drug-resistant cells [143]. The hybridization of CpG oligonucleotide onto pristine SWCNT was used as a strategy to enhance the cell internalization and thus the activation of the innate immune system via Toll-like receptor 9 in a malignant brain cancer model [144]. As a consequence, a selective inhibition of glioma cells migration was observed, while macrophages viability and proliferation remained almost unaltered.…”
Section: Pristine and Non-covalently Functionalized Cnmentioning
confidence: 99%